HIV antigen and antibody detection: variable responses to infection in the Edinburgh haemophiliac cohort. Issue 6622 (27th February 1988) - Simmonds, P; Lainson, F A L; Cuthbert, R; Steel, C M; Peutherer, J F; Ludlam, C A
Abstract : Sequential serum samples from 18 haemophiliac patients exposed simultaneously to human immunodeficiency virus type 1 (HIV 1) in early 1984 were tested retrospectively for serological markers of infection. Assay for total antibodies to HIV established that the time to seroconversion might be as long as 110 days after exposure to contaminated factor VIII; serum samples were also tested by Western blotting, by enzyme linked immunosorbent assay (ELISA) for specific antibodies to envelope and core proteins, and for p24 antigen by two assay systems during the two years after infection. The studies showed that five of the 12 patients for whom serum samples obtained between exposure and seroconversion were available had transient p24 antigenaemia. Although amounts of total antibody to HIV and of antibodies to envelope proteins rose continuously during the two years of the study, amounts of antibody to the core protein were variable and tended to decline in patients who became symptomatic. Two patients had persistent p24 antigenaemia that began four months after seroconversion; these patients remained asymptomatic. One patient who developed the acquired immune deficiency syndrome (AIDS) had transient antigenaemia at the time of seroconversion but failed to show any antigen for the rest of the study; progression to AIDS was accompanied by an increase in antibodies to envelope proteins. Much of the variability in the course of infection with HIV must represent the differences in the susceptibility of the patients to infection.